Hubungan Tingkat Pengetahuan Ibu Nifas Tentang Perawatan Luka Perineum Dengan Lama Penyembuhan Luka Di Wilayah Kerja Puskesmas Koto Baru - Nedean, Oktorelia; Sari, Evin Noviana; Hafiza, Hafiza (Akademi Kebidanan Bunga Husada Samarinda, 2023)
Perineal injuries are perineal injuries to the urogenital diaphragm and laterol ani muscles, which occur during normal delivery. Rupture is a wound in the perineum caused by natural tissue damage due to the process of pressing the fetal head or shoulder during a normal delivery process, while an episiotomy is a surgical incision in the perineum to enlarge the opening of the vagina which is done right next to the exit of the baby's head (Nurrahmaton, 2019). This study uses a descriptive analytic method, namely a study that describes, analyzes and links between the independent variables and the dependent variable. The design of this study was with a cross-sectional design, the relationship between the knowledge of postpartum mothers and healing of perineal wounds in the work area of ​​the Koto Baru Health Center, Dharmasraya Regency in 2023, almost all of them, namely 23 respondents (57.5%) who had less knowledge, experienced healing of old wounds of postpartum mothers who had good knowledge, almost half of them were 11 people. (27.5%), while a small proportion of those who are knowledgeable are 6 people (15.0%). Based on statistical tests using the Chi Square test, the results obtained are P value 0.000 (P value 0.05) meaning that there is a significant significant relationship between mother's knowledge with the duration of wound healing in the Work Area of ​​the Koto Baru Health Center, Dharmasraya Regency in 2023. It is recommended that health workers provide counseling regarding the knowledge of postpartum mothers regarding perineal wound care and wound healing time so that they can increase mother's knowledge regarding wound care.